COMPARATIVE EVALUATION OF VENTRAL MESH RECTOPEXY AND LAPAROSCOPIC POSTERIOR RECTOPEXY IN THE TREATMENT OF FULL-THICKNESS RECTAL PROLAPSE - Madinabonu Shamsiddinova Shukhrat kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Background: Rectal prolapse remains a challenging condition in colorectal surgery, with multiple surgical options and no universal standard. Minimally invasive abdominal procedures, particularly ventral mesh rectopexy (VMR) and laparoscopic posterior rectopexy (LPR), are increasingly considered optimal approaches due to low recurrence and favorable functional outcomes. Objective: To compare early and long-term outcomes of ventral mesh rectopexy and laparoscopic posterior rectopexy without resection in patients with full-thickness rectal prolapse. Methods: A prospective comparative study included 54 patients with complete rectal prolapse. Patients were divided into two groups: Group A (n=27) underwent ventral mesh rectopexy, Group B (n=27) underwent laparoscopic posterior rectopexy without resection. Outcomes assessed included operative time, blood loss, postoperative complications, length of hospital stay, recurrence rate, and functional outcomes (constipation and fecal incontinence scores) at 12 and 24 months. Results: VMR demonstrated significantly better improvement in constipation and incontinence scores, with lower recurrence rates compared to posterior rectopexy. Posterior rectopexy showed shorter operative time but higher incidence of postoperative constipation. Conclusion: Ventral mesh rectopexy provides superior functional outcomes and lower recurrence rates compared to laparoscopic posterior rectopexy, particularly in patients with associated pelvic floor dysfunction.